Systematic Literature Review: Pembelajaran Volume Kubus di Sekolah Dasar - Rohatul Fikriyah Safira; Putri Aini, Rabeca; Marzan Shaffiyah, Sekar (Papanda Journal of Mathematics and Science Research, 2024)
In learning Mathematics in Elementary Schools there is material about the volume of a cube. The volume of the cube is a material discussion that aims to determine the amount of space occupied by substances, such as solids, liquids, and gases. This study uses the concept of a literature review with a Systematic Literature Review (SLR) technique. This collection technique is carried out by reviewing all articles related to the volume of cube space in the 2017-2021 time span. The articles used in this study were 30 journal articles obtained from Google Scholar and Garuda. Based on research with data analysis that has been done the learning model that is widely applied in learning the volume of the cube is the Contextual Approach Learning Model, Discovery Learning, Guided Inquiry, and Realistic Mathematics Education (RME) and the most widely used learning media is the Unit Cube Teaching Aid. By studying the volume of building materials, it can improve the learning outcomes of elementary school students